Medication adherence and hopelessness in male individuals with substance use disorder - Kargin, Maral; Ersogutcu, Filiz; Aslanoglu, Eren (Taylor & Francis Inc, 2021)
Objectives: This descriptive study was conducted to examine the levels of hopelessness and medication adherence in individuals diagnosed with substance use disorder. Methods: The study was conducted at the Alcohol and Substance Use Treatment Center service of a psychiatry clinic in Turkey. The study included 100 male patients. In terms of data collection, the following were used: personal information form Beck Hopelessness Scale and Morisky Medication Adherence Scale. In the analysis of the data, number, percentage and mean, t-test, ANOVA and correlation in independent groups were used by using SPSS 22 software. Results: This study established that the mean score of the patients from the hopelessness was 6,22 +/- 4,07, and the mean score of the medication adherence was shown as 6,65 +/- 1,15. This study observed a negative relationship between total hopelessness score and medication adherence score. There was a positive correlation between hopelessness total score and age. It was determined that there was a significantly negative relationship between substance use duration, age and total medicatio n adherence score. Conclusion: The findings of the study showed that medication adherence decreased with increasing hopelessness. In addition it was determined that as age and substance use increased, hopelessness increased and adherence to treatment decreased.
Keywords: Substance use; nursing; hopelessness; medication adherence